2015
DOI: 10.1016/j.ejpb.2014.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous silica as topical nanocarriers for quercetin: characterization and in vitro studies

Abstract: The flavonoid quercetin is extensively studied for its antioxidant and chemopreventive properties.However the poor water-solubility, low stability and short half-life could restrict its use in skin care products and therapy.The present study is aimed to evaluate the potential of aminopropyl functionalized mesoporous silica nanoparticles (NH 2 -MSN) as topical carrier system for quercetin delivery. Thermo gravimetric analysis, X-ray diffraction, high resolution transmission electron microscopy, nitrogen adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(91 citation statements)
references
References 63 publications
2
84
0
Order By: Relevance
“…Indeed, many studies have shown that these compounds have anticancer activities against various cancer cells such as colon, prostate, skin, glioma and breast cancer cells. [13][14][15] However pharmaceutical applications of phenolic compounds in general are severely hampered by their unsatisfactory bioavailability, due to poor water solubility, low stability and short half-life. 15,16 In addition, the biological activity of these natural products can be affected by physicochemical factors such as light, oxygen/air, humidity or other reactive compounds from the environment.…”
Section: 12mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many studies have shown that these compounds have anticancer activities against various cancer cells such as colon, prostate, skin, glioma and breast cancer cells. [13][14][15] However pharmaceutical applications of phenolic compounds in general are severely hampered by their unsatisfactory bioavailability, due to poor water solubility, low stability and short half-life. 15,16 In addition, the biological activity of these natural products can be affected by physicochemical factors such as light, oxygen/air, humidity or other reactive compounds from the environment.…”
Section: 12mentioning
confidence: 99%
“…[13][14][15] However pharmaceutical applications of phenolic compounds in general are severely hampered by their unsatisfactory bioavailability, due to poor water solubility, low stability and short half-life. 15,16 In addition, the biological activity of these natural products can be affected by physicochemical factors such as light, oxygen/air, humidity or other reactive compounds from the environment. In order to protect these bioactive compounds against degradation and to enhance their bioavailability, in recent years various encapsulation and complexation methods have been explored.…”
Section: 12mentioning
confidence: 99%
“…Thus, loading of flavanols in nanoporous silica systems can stabilize and protect them from degradation, ensuring high loading capacity [22][23][24][25][26][27]. Preliminary studies show that immobilization of quercetin in the mesoporous silica, like MCM-41, successfully stabilized quercetin, improving its antioxidant efficacy [28,29,31]. In addition, the increased specific surface area of mesoporous silica particles could eventually improve the bioavailability of bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, silica nanoparticles with an average size less than 25 nm can penetrate but could not permeate the skin [24]. As the vehicles of quercetin, MSNs with an average size of 250 nm can facilitate drug penetration in the skin while without transdermal delivery [26]. This could be due to the barrier property of stratum corneum.…”
Section: Discussionmentioning
confidence: 99%